2020
DOI: 10.1080/10407782.2020.1713694
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of flow pattern and temperature profiles by residence time distribution in typical structured packed beds

Abstract: The flow and temperature fields in packed beds are rather complex but are of great importance since they will influence macroscopic parameters and the overall performance of the packed bed system. Regions with either too high or too low velocity are not preferred since they will decrease the heat and mass transfer characteristics of packed beds. The residence time distribution (RTD) is a way to assess the characteristics of the flow maldistribution, where a narrower distribution is closer to the ideal plug flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…The tracer concentration of the fluid domain is calculated and followed until it completely exits the outlet. The duration time of the tracer injection should be lower than 1% of the whole mean residence time [15]. The time step used in the present study is 5×10 -5 s. The convergence of each time step is reached when the residual of the tracer concentration is less than 10 -6 and the total time step of the calculation is 10000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tracer concentration of the fluid domain is calculated and followed until it completely exits the outlet. The duration time of the tracer injection should be lower than 1% of the whole mean residence time [15]. The time step used in the present study is 5×10 -5 s. The convergence of each time step is reached when the residual of the tracer concentration is less than 10 -6 and the total time step of the calculation is 10000.…”
Section: Methodsmentioning
confidence: 99%
“…Guo et al [14] revealed that there is a relationship between the velocity distribution on a cross section and the RTD curve. Wang et al [15] studied the RTD in three typical structured packed bed and reported a relationship between the RTD and the heat transfer. Stepanov et al [16] studied the residence time by Lagrange particle tracking method in CFD to determine the influence of baffles in a combustion chamber.…”
Section: Introductionmentioning
confidence: 99%
“…纵向波纹内翅片管被用于空分系统冷却器(图10), 替 代原设计选用的整体轧制翅片管, 既提高了换热性 能, 又显著减小了换热器体积, 设备重量仅为原来的 1/4~1/3, 大幅降低了制造成本. [34,39] . 停留时间分布方差(VRTD)越小, 说明孔 隙结构中的流动越接近于理想推流, 对应的推流度越 高, 流动分布越均匀.…”
Section: 然而现有热力设计方法在节能和储能传递过程中unclassified
“…The impacts of viscosity, velocity profile, and residence time gradients on outputs from thermal polymerization systems in continuous flow reactors has been investigated. , Based on these learnings, Corrigan et al investigated similar effects for PET-RAFT polymerization, aiming to tune and manipulate the shape of molecular weight distributions in PET-RAFT (Figure A). It was noted that several approaches could be used (e.g., the flow rates of the reactant streams, the chemical concentrations entering the reactor) to produce polymeric products with tailored molecular weights.…”
Section: High Throughput Synthesis: Turning Monomers Into Biofunction...mentioning
confidence: 99%